Coaching Clinic Penggunaan Media Asesmen Digital Berbasis Website sebagai Sarana Evaluasi Pembelajaran di SDN 4 Suntalangu - Gilang Primajati; Lu’luilmaknun, Ulfa; Supiarmo, M.Gunawan; Oktavihari, Dita; Apriliska, Sasa (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
SDN 4 Suntalangu is a school located at the foot of Mount Rinjani, precisely in Suela Sub-district, East Lombok Regency. The limitations of facilities and the lack of technologically literate educators in keeping up with current developments are important issues to note. Therefore, the implementation of a coaching clinic program on the use of website-based digital assessment media as an evaluation tool is a necessity for teachers at SDN 4 Suntalangu in order to enhance their skills in utilizing digital technology as a means of learning evaluation. In the digital era, website-based assessments offer an efficient and practical alternative compared to conventional methods such as paper-based assessments. There are many advantages to conducting digital, website-based learning evaluations, including making the learning process more engaging since students can learn visually and directly. Moreover, assessment results can be obtained in real time, so teachers no longer have to manually grade each student’s work one by one. However, many teachers still face limited understanding in designing and using digital assessment media, which leads to less optimal learning evaluation. The purpose of this program is to equip teachers with the knowledge and skills to use website-based assessment media, to improve the quality of learning evaluation, and to support the achievement of a more effective and modern learning process. The implementation method of this program consists of three main stages. First, the socialization stage to introduce the concept and benefits of digital assessment media. Second, technical training (hands-on training) to teach how to create and manage website-based assessments using both free and paid platforms. Third, intensive mentoring to assist teachers in implementing these assessment tools in classroom learning. The expected outcomes of this community service program include scientific publications in ISSN-registered journals and the dissemination of results online through the Mathematics Education Study Program website, which is connected to the Faculty of Teacher Training and Education (FKIP) website at the University of Mataram. An additional expected outcome is the utilization of the website-based assessment applications/programs developed through this program in classes of certain courses.